Velocity and abundance precisions for future high‐resolution spectroscopic surveys: A study for 4MOST. Issue 3 (1st March 2013) - Caffau, E.; Koch, A.; Sbordone, L.; Sartoretti, P.; Hansen, C.J.; Royer, F.; Leclerc, N.; Bonifacio, P.; Christlieb, N.; Ludwig, H.‐G.; Grebel, E.K.; de Jong, R.S.; et al.
Abstract In preparation for future, large‐scale, multi‐object, high‐resolution spectroscopic surveys of the Galaxy, we present a series of tests of the precision in radial velocity and chemical abundances that any such project can achieve at a 4 m class telescope. We briefly discuss a number of science cases that aim at studying the chemo‐dynamical history of the major Galactic components (bulge, thin and thick disks, and halo) – either as a follow‐up to the Gaia mission or on their own merits. Based on a large grid of synthetic spectra that cover the full range in stellar parameters of typical survey targets, we devise an optimal wavelength range and argue for a moderately high‐resolution spectrograph. As a result, the kinematic precision is not limited by any of these factors, but will practically only suffer from systematic effects, easily reaching uncertainties <1km s–1. Under realistic survey conditions (namely, considering stars brighter than r = 16 mag with reasonable exposure times) we prefer an ideal resolving power of R ∼20 000 on average, for an overall wavelength range (with a common two‐arm spectrograph design) of [395;456.5] nm and [587;673] nm. We show for the first time on a general basis that it is possible to measure chemical abundance ratios to better than 0.1 dex for many species (Fe, Mg, Si, Ca, Ti, Na, Al, V, Cr, Mn, Co, Ni, Y, Ba, Nd, Eu) and to an accuracy of about 0.2 dex for other species such as Zr, La, and Sr. While our feasibility study was explicitly carried out for the 4MOST facility, the results can be readily applied to and used for any other conceptual design study for high‐resolution spectrographs. (© 2013 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)